Tingkat Penerimaan Aplikasi SIHA 2.1 pada Petugas Kesehatan di Provinsi Jawa Tengah - Diah Kari Artati; Lutfiyah Rizqulloh; Destri Maya Rani (Politeknik Negeri Jember, 2024)
The SIHA application is the official platform for recording and reporting HIV/AIDS and IMS at the national, district, and provincial administrative levels. Since 2012, SIHA has been used by the health office but in its application, there are still frequent problems, especially when inputting patient data and sending reports that often experience errors. In addition, this application can only be accessed using Mozilla Firefox. At the beginning of the emergence of SIHA until 2023, there has never been an evaluation. The purpose of the study was to identify the level of acceptance of the SIHA 2.1 application among health workers in 3 (three) districts/cities in Central Java Province, namely Semarang, Jepara, and Grobokan. A cross-sectional design was used in this study and the sample selection technique used a non-probability sampling technique with an accidental sampling method. So that the number of samples that fit the researcher's criteria was 56 people. The results showed that there is a significant relationship between Performance Expectancy, Effort Expectancy, and Price Value related to health workers' interest in implementing the SIHA 2.1 application. As for Hedonic Motivation, there is no significant relationship. It is expected that the development of the SIHA 2.1 application to further improve services to minimize the occurrence of errors in the use of information systems for recording and reporting HIV/AIDS data and to simplify the filling of the SIHA 2.1 application.